2021
DOI: 10.1021/acssensors.1c01344
|View full text |Cite
|
Sign up to set email alerts
|

Catching COVID: Engineering Peptide-Modified Surface-Enhanced Raman Spectroscopy Sensors for SARS-CoV-2

Abstract: COVID-19 remains an ongoing issue across the globe, highlighting the need for a rapid, selective, and accurate sensor for SARS-CoV-2 and its emerging variants. The chemical specificity and signal amplification of surface-enhanced Raman spectroscopy (SERS) could be advantageous for developing a quantitative assay for SARS-CoV-2 with improved speed and accuracy over current testing methods. Here, we have tackled the challenges associated with SERS detection of viruses. As viruses are large, multicomponent specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Interestingly, the Raman range, which was noticed in this work, coincides with the position of the peak that was used to test the anti-SARS-CoV-2 IgM/IgG level using the SERS technique (1328 cm -1 ) [22] . Moreover, Payne et al, showed, that the strongest peaks corresponding to spike proteins from COVID-19 were located in the Raman range, which was used to differentiate samples in this work [45] . Also, Carlomagno et al, showed, that peak in the Raman spectrum located at 1317 cm -1 , which is originated from structural proteins of COVID-19 can be used to differentiate samples collected from people with positive and negative results of COVID-19 test [46] .…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, the Raman range, which was noticed in this work, coincides with the position of the peak that was used to test the anti-SARS-CoV-2 IgM/IgG level using the SERS technique (1328 cm -1 ) [22] . Moreover, Payne et al, showed, that the strongest peaks corresponding to spike proteins from COVID-19 were located in the Raman range, which was used to differentiate samples in this work [45] . Also, Carlomagno et al, showed, that peak in the Raman spectrum located at 1317 cm -1 , which is originated from structural proteins of COVID-19 can be used to differentiate samples collected from people with positive and negative results of COVID-19 test [46] .…”
Section: Discussionmentioning
confidence: 75%
“…SERS is an effective technique for the sensitive detection of biomolecules, and various SERS-based immunoassays have thus been developed for the detection of infectious viruses ( Saviñon-Flores et al, 2021 ). Following the emergence of the COVID-19 pandemic, several SERS-based methods for SARS-CoV-2 have been applied ( Zhang et al, 2021 ; Wu et al, 2022 ; Yang et al, 2021 ; Yu et al, 2021 ; Srivastav et al, 2021 ; Sanchez et al, 2021 ; Payne et al, 2021 ; Liu et al, 2021 ; Li et al, 2021 ; Huang et al, 2021 ; Gao et al, 2021 ; Chen et al, 2021 ; Chen et al, 2021 , 2021 ; Huang et al, 2021 , 2021 ; Pramanik et al, 2021 ; Zavyalova et al, 2021 ). However, the current magnetically assisted SERS immunoassay is the only assay developed so far that facilitates the on-site diagnosis of the samples of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advancements in SERS have led to the development of sophisticated sensing methods that facilitate precise analysis and generation of high-quality SERS-active nanostructures ( Hwang et al, 2019 ; Shin et al, 2018 ). In particular for the combat with COVID-19, SERS technology has not only exhibited less time-cost advantages than PCR for detection SARS-CoV-2 and antibodies, but also exhibited more advantages such as identifying infectiousness of SARS-CoV-2 ( Peng et al, 2021a , Peng et al, 2021b ; Zhang et al, 2021 ; Wu et al, 2022 ; Yang et al, 2021 ; Yu et al, 2021 ; Srivastav et al, 2021 ; Sanchez et al, 2021 ; Payne et al, 2021 ; Liu et al, 2021 ; Li et al, 2021 ; Huang et al, 2021 ; Gao et al, 2021 ; Chen et al, 2021 ; Chen et al, 2021 , 2021 ; Huang et al, 2021 , 2021 ; Pramanik et al, 2021 ; Zavyalova et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Type of Biosensor Testing Sample Assay Time (min) LOD Ref. Electrochemical saliva 6.5 229 fg mL −1 [ 80 ] Electrochemical saliva 4 2.8 fg mL −1 [ 81 ] Electrochemical saliva 60 0.35 ag mL −1 [ 82 ] Colorimetric NP/OP 5 0.154 pg mL −1 [ 83 ] Colorimetricr NP/OP 30 4.98 ng mL −1 [ 84 ] Colorimetric NP/OP 5 100 pfu mL −1 [ 85 ] SERS 300 nM [ 89 ] SERS urines 5 80 copies mL −1 [ 90 ] Nano biofluids 0.08 12.6 nM [ 93 ] FET PBS 20 165 copies mL −1 [ ...…”
Section: Ace2-based Biosensors For Sars-cov-2 Detectionmentioning
confidence: 99%